Residual stress measurement in AlSi alloys: Eigenspannungsmessung an einer AlSi‐Legierung. Issue 12 (10th January 2018) - Reisgen, U.; Sharma, R.; Gach, S.; Olschok, S.; Francis, J.; Bobzin, K.; Oete, M.; Wiesner, S.; Knoch, M.; Schmidt, A.
Abstract: In this work, the relaxation of residual stresses inside a sample made of the aluminum alloy AlSi7Mg0.3 after tempering is described. The comparison of stress evaluation by X‐ray diffraction and incremental hole drilling method combined with electronic speckle pattern interferometry strain determination gives the opportunity to evaluate micro stresses together with first order macro stresses. Compressive stresses within the surface of a cold worked sample are relaxed by tempering. The X‐ray diffraction evaluation is supported by the analysis of a stress‐free sample through incremental hole drilling method.